Oxidation of Catechol using Titanium Silicate (TS-1) Catalyst: Modeling and Optimization - Sonali Sengupta; Debarpita Ghosal; Jayanta K. Basu (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2013)
The oxidation of catechol was studied in an eco-friendly process with commercial titanium silicate-1 (TS-1) catalyst and hydrogen peroxide as oxidant in absence of all mass transfer effects. The process was opti-mized by Box-Behnken design in terms of three independent process variables such as reaction tempera-ture, moles of hydrogen peroxide per mole of catechol and catalyst amount whose optimum values of the process variables were found to be 60 °C, 13.2 and 1.24 g respectively for maximum conversion of 75.8 %. The effects of different process parameters such as mole ratio of hydrogen peroxide to catechol, catalyst par-ticle size, catalyst amount, temperature and reaction time were studied. A pseudo first order kinetic model was fitted with the experimental rate data. The apparent activation energy for the reaction was found to be 11.37 kJ/mole. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)